TECHNO ECONOMIC ANALYSIS OF BIOMASS AS AN ALTERNATIVE ENERGY HOUSEHOLDS AND SMALL INDUSTRIES - Dewi, Rany Puspita; Trisma Jaya Saputra; Mario Ammar Rasyid (Jurnal Rekayasa Mesin, 2024)
Briquetting technology became one appropriate method that can be used to convert biomass waste into a renewable energy source. Sources of biomass raw materials that have promising potential are pine sawdust and coconut shell waste. Sawdust has potential for about 0.78 million m3/year and coconut shell waste around 360 thousand tons/year. The research aim was to analyze the effect of the carbonization temperature to volatile matter and fixed carbon of briquette. The research was done by variating carbonization temperature at 400oC, 500oC, and 600oC. The result showed that at carbonization temperature of 400oC, the volatile matter and fixed carbon was 42.28% and 55.74%. The volatile matter and fixed carbon are 43.19% and 54.96%, found at carbonization temperature 500oC. The highest fixed carbon 55.98% and the lowest volatile matter 42.19% was found from carbonization temperature at 600oC. The carbonization temperature in briquetting process affect the volatile matter and fixed carbon of briquette